A escolarização de jovens e adultos trabalhadores no município de Carangola/MG - Andrade, Elizete Oliveira de (2006)
The present study aims to analyse the process of schooling of adult people within the municipal educational system of Carangola/MG, as well as understand their perceptions relative to the learning process they experience. The purpose is to understand the reasons for the high rates of repetition and dropping out within that system in the municipality in question, from the perspective of the participants. The subjects of the study were adult students attending the first part of primary education (first four years) at the Escola Municipal Antonio Marques, as well as those attending two classes that deal with students from many levels, located in a state school in that same municipality. The field work was developed in interdependent stages that included: the selection of the sample of the unity under study; the analysis of local context; the application of the questionnaire and the interviewing process to students and teachers; the formation of a group of study with the teachers that were the subjects of the research; participant observation in classes; and gathering and analysing of data. We conclude pointing out elements that should be borne in mind in order to rethink about the schooling process of those students in the municipality focused in the study. The need is emphasised for public policies to prioritise that segment of the population, which has been historically excluded from the education system due to its low quality.